2019
DOI: 10.3389/fphar.2019.00397
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA ZEB1-AS1 Mediates Oxidative Low-Density Lipoprotein-Mediated Endothelial Cells Injury by Post-transcriptional Stabilization of NOD2

Abstract: Oxidized-low density lipoprotein (ox-LDL) can induce injury of endothelial cells, causing atherosclerosis, which is an important initial event in several cardiovascular diseases. Long non-coding RNAs (lncRNAs) have emerged as regulators of diverse biological processes, but their specific biological functions and biochemical mechanisms in ox-LDL-induced endothelial cell injury have not been well investigated. Here, we describe the initial functional analysis of a poorly characterized human lncRNA ZEB1 antisense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…[6][7][8] Furthermore, lncRNAs have been reported to play a role in the ox-LDL-induced cell processes associated with human diseases. 9,10 Also, lncRNA OIP5-AS1 promotes the apoptosis of ox-LDL-induced vascular endothelial cells by regulating GSK-3b, 11 meaning that OIP5-AS1 is related to the functional mechanism of ox-LDL. However, the role of OIP5-AS1 in ox-LDL-induced macrophages is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Furthermore, lncRNAs have been reported to play a role in the ox-LDL-induced cell processes associated with human diseases. 9,10 Also, lncRNA OIP5-AS1 promotes the apoptosis of ox-LDL-induced vascular endothelial cells by regulating GSK-3b, 11 meaning that OIP5-AS1 is related to the functional mechanism of ox-LDL. However, the role of OIP5-AS1 in ox-LDL-induced macrophages is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The report of Xu et al . revealed that Nod2 downregulation could mitigate endothelial cell injury induced by ox-LDL [ 19 ]. Also, the reduction of Nod2 caused by long noncoding RNA XIST inhibition could attenuate endothelial cell injury by repressing apoptosis and promoting the viability of ox-LDL-induced umbilical vein endothelial cells [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was claimed that Nod2 plays vital roles in the inflammatory process of AS [ 17 ]. Also, Nod2 was revealed to be connected with endothelial cell reactive oxygen species (ROS) generation [ 18 ] and injury [ 19 , 20 ]. However, the molecular mechanisms associated with Nod2 in AS have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the lncRNA Meg3 was consider as a protective element during the injury process of the vascular endothelial cells [23]. However, the lncRNA ZEB1-AS1 enhanced the oxidative low-density lipoprotein induced damage of the vascular endothelial cells [24]. The lncRNA NEAT1 has shown that could suppressed the oxidative stress induced injury of vascular endothelial cells by activating the miR181d-5p/CDKN3 [25].…”
Section: Discussionmentioning
confidence: 99%